Effect of Regional Original Revenue, General Allocation Fund, and Revenue Sharing Fund on Capital Expenditure and Their Impact on Economic Growth in Kutai Kartanegara Regency - Romadlona, Fitria; Wijaya, Adi; Suharto, Rahcmad Budi (Budapest International Research and Critics University, 2022)
The purpose of this study to discuss about effect of regional original revenue, general allocation fund, and revenue sharing fund on capital expenditure and their impact on economic growth in Kutai Kartanegara Regency. This research is quantitative descriptive. The data used is secondary data obtained from the Audited Financial Report of the Regional Government of Kutai Kartanegara Regency from 2007 to 2021 and the Central Bureau of Statistics of East Kalimantan Province. The analytical method in this study uses multiple linear regression analysis and path analysis. The research results show that directly, regional original revenue and general allocation fund have no significant effect on capital expenditure, while revenue sharing fund has significant effect on capital expenditure. Regional original revenue, general allocation fund, revenue sharing fund, and capital expenditure have no significant effect on economic growth. Indirectly, regional original revenue and general allocation fund have significant effect on economic growth through capital expenditure. Revenue sharing fund has no significant effect on economic growth through capital expenditure.